POSITION AND FUNCTION OF MONITORING SYSTEM ON LOCAL GOVERNMENT FINANCIAL PERFORMANCE - Rusli, Damay (Sean Institute, 2023)
Law Number 17 of 2003 concerning State Finances mandates the Government to prepare Regional Government Financial Reports consisting of Budget Realization Reports, Cash Flow Reports, Balance Sheets, Notes to Financial Statements, SAL Reports, Operational Reports, and Reports on Changes in Equity. The financial reports prepared and presented by the local government (pemda) are structured reports that describe the financial position as well as financial and non-financial transactions that are carried out each year. These financial statements are prepared with the aim of presenting information regarding the financial position, budget realization, budget surplus, cash flows, results of operations, and changes in equity of a reporting entity which is expected to provide benefits to users in making and evaluating decisions regarding the allocation of resources. This study uses descriptive analysis as a research method, using a qualitative approach, while the results of the research explain that, the existence of assessment and supervision of local governments can actually be a parameter that spurs local governments to be more careful, thorough and professional in spending regional finances thus Good governance will be implemented, namely a government that is free from corruption, collusion and nepotism.